ANALYZING STUDENTS’ SPEAKING ERRORS: A STUDY OF INTERACTION IN ONE-TO-ONE EFL CLASSROOM - Tamelab, Maryance Ferawati (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
AbstractThis study investigates verbal errors in the context of English as a Foreign Language (EFL) instruction in a one-on-one classroom. Al Hosni (2014) states that the ability to speak English as a means of communication is crucial for individuals pursuing advancement in a variety of human endeavors. However, incorporating this complex talent into the teaching of English as a foreign language presents difficulties. Despite exposure to the language across multiple educational levels, EFL students frequently struggle to acquire the fundamentals of English proficiency, particularly in speaking classes. These obstacles include a lack of lexicon, difficulties with pronunciation, and grammatical uncertainty, which result in the emergence of errors during the learning process (Chou, 2018). Observational methods were used to acquire data during teaching and learning sessions, with the aid of an audio recorder. Approximately 7 hours and 6 minutes' worth of audio recordings were obtained in total. Using the interactive model (Miles & Crisp, 2014), the collected data were subsequently analyzed. The findings revealed a total of 315 errors generated by the participants, each resulting from student participation and including at least one grammatical, lexical, or phonological error as well as the use of the first language without request. The findings included the number and percentage of errors discovered during the data analysis. In conclusion, this study provides valuable insights into the common types of errors made by EFL learners in a one-on-one classroom. Grammatical, phonological, and lexical errors were identified as the most common. The importance of the teacher's role in guiding students through the process of language acquisition is emphasized. In addition, the study highlights the unique dynamics of one-on-one interactions, in which students feel more at ease experimenting with language and actively partaking in their learning process. This research contributes to the educational landscape by advocating for a holistic approach to language learning in which mistakes are not barriers to effective communication but rather stepping stones.